“Exploring Milestones”: Harnessing active learning in the undergraduate paediatrics curriculum - Chhaya Divecha; Miriam Simon; Ciraj Mohammed (The Asia Pacific Scholar)
Introduction: Paediatric milestones provide a structured method for observing and monitoring a child’s progress and should be part of core paediatric curriculum. However, a literature review reveals that primary care physicians and pediatricians feel inadequate about their knowledge and practice of developmental paediatrics, thus exposing the lacunae in training. Methods: An intervention was planned amongst final-year medical undergraduate students in Oman during their paediatric rotation. A 90-minute multimodal active learning module incorporating diverse learning orientations was planned and administered as a skill-lab session. Its effectiveness in learner motivation, engagement, and faculty participation was evaluated using a questionnaire based on the ICAP (Interactive, Constructive, Active, and Passive) framework, administered to students at the end of the session. Results: Responses of the 62 participants indicated a significant association between their overall experience and tasks related to the active, constructive, and interactive elements of the module (p=0.001). The faculty’s role in facilitating the session significantly contributed to students’ overall experience (p=0.000). On linear regression, active, constructive, and interactive components of the module were moderate to high predictors of the participants’ overall learning experience. Conclusion: It was beneficial to base the teaching module on established learning theories. Active learning strategies proactively fostered student engagement and self-directed learning during the session. Faculty played an important role in planning and customising the content, flow, and delivery to maximise meaningful learning. Such interactive collaboration, especially for theoretical concepts in medicine, enables better student engagement, providing enhanced opportunities for learning, practice, and feedback.